Post-fire response variability in Mediterranean Basin tree species in Portugal - Catry, Filipe X.; Pausas, Juli G.; Moreira, Francisco; Fernandes, Paulo M.; Rego, Francisco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2013)
Fire is the most important natural disturbance driving vegetation dynamics in the Mediterranean Basin. However, studies relating fire-induced tree responses to both fire severity and plant traits are still scarce in this region. We aimed to investigate such relationships further and to develop simple models that could help improve forest management in these fire-prone ecosystems. We compiled data from 16 fire sites in different regions and used models to relate post-fire responses of 4155 trees from 14 species with fire severity indicators and tree characteristics. The influence of several spatiotemporal factors at the site level was also considered. Results showed that pine mortality was usually high and mainly determined by fire severity, whereas plant traits played a minor role. In contrast, mortality of broadleaved trees was usually low, even for high-severity fire, but most trees were top-killed. Stem mortality increased with fire severity and decreased with bark thickness and tree size. The models for predicting individual mortality of pines and stem mortality of broadleaves showed very good performance, including when validated against independent datasets. Our results suggest that it is possible to accurately predict the most common post-fire responses of Mediterranean species based on simple fire and tree characteristics.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: broadleaves; experimental fire; Modelling; mortality; pines; top-kill; Wildfire

Laboratory characterization of firebrands involved in spot fires - Ganteaume, Anne; Guijarro, Mercedes; Jappiot, Marielle; Hernando, Carmen; Lampin-Maillet, Corinne; Pérez-Gorostiaga, Pedro; Vega, José a (Annals of Forest Science, 2011)
& Introduction Wildfires are considered the most important disturbance in the Mediterranean Basin, and some are propagated over long distances due to lift-off and ignition of firebrands. & Objectives To improve our knowledge of firebrands involved in spotting fires, flammability characteristics of eight types of firebrands commonly generated by wildfires in Southern Europe were determined under laboratory conditions. & Results All the firebrands tested showed 100% ignition frequency but with a wide range of time to ignition and flaming duration. Weight loss during combustion was exponentially related to time, and there was a decrease in the ratio of the weight at temperature T to the initial weight with increasing temperatures. In our experimental conditions, there was a significant effect of fuel moisture content on time to ignition, flaming duration, combustion and thermal decomposition. On the basis of the characteristics analysed, three firebrand groups have been identified in relation to spotting: heavy firebrands with ability to sustain flames, efficient for long-distance spotting (pine cones); light firebrands with high surface-to-volume ratio, efficient for short-distance spotting (leaves and thin barks); and light firebrands with low surface-to-volume ratio, efficient for short and, occasionally, long-distance spotting (all the other types of firebands).
Keywords: ember; Fire behaviour; firebrand; flammability parameters; Wildfire

Post-fire recolonisation of a montado area by the endangered Cabrera vole (Microtus cabrerae) - do Rosario, Ines T.; Mathias, Maria Da Luz (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2007)
The Cabrera vole is an endangered species frequently found in the montado, a savannah-like ecosystem well adapted to fire. Although it is assumed that regular burning is not very prejudicial to this vole, the impact of fire is unknown. This research studied, for the first time, recolonisation by the Cabrera vole after wildfire. Colonies were monitored over one year after a wildfire and the most relevant ecological features in their reestablishment were identified. During the first eight months, all the 18 surveyed colonies remained unoccupied. However, after one year, 11 were recolonised. Vegetation structure and composition in the colonies ( vegetation height, plant families diversity, percentage of bare ground and cover of shrubs before the fire), which are important features in offering protection and nutrition, were closely related to reoccupation of the colonies. Surprisingly, fire intensity did not influence recolonisation. Distance from unburned areas proved to be a factor that delayed recolonisation. The importance of the montado for this species was reinforced by the evidence that recolonisation occurred preferentially in colonies surrounded by this habitat type.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: CAP procedure; distance to unburned areas; MDS; Mediterranean; Portugal; Wildfire